2018
DOI: 10.29245/2689-9981/2018/3.1122
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Associated Pneumonia in Adult Patients Preventive Measures: A Review of the Recent Advances

Abstract: Ventilator Associated Pneumonia (VAP) is the most commonly acquired ICU infection worldwide affecting nearly 10-30% of ventilated patients and accounting for nearly 25% of all types of ICU infections. VAP has been associated with increased morbidity, mortality, duration of ICU stay, duration of mechanical ventilation and nearly 50% of the ICU antibiotic prescription. After understanding the pathogenesis of VAP, various preventive measures have been tried by various authors. The currently accepted preventive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
2
3
1
Order By: Relevance
“…Similar results from a study conducted in India revealed that assessment of redness to extubate, trial extubation, maintenance of ETT cuff pressure, and suctioning were the roles in preventing VAP (17).…”
Section: Strategies Used For Preventing Vap Among Critically Ill Pati...supporting
confidence: 64%
See 1 more Smart Citation
“…Similar results from a study conducted in India revealed that assessment of redness to extubate, trial extubation, maintenance of ETT cuff pressure, and suctioning were the roles in preventing VAP (17).…”
Section: Strategies Used For Preventing Vap Among Critically Ill Pati...supporting
confidence: 64%
“…Furthermore, the study has revealed early weaning, head of bed elevation of 30-45º, oral care, administration of medication (antibiotics/prophylaxis), and implementation of IPC measures as the common nursing interventions for VAP prevention. This shows that nurses were implementing the VAP bundle components in their setting, In support of the above ndings, previous work from the India, USA, and Spain revealed that early weaning, head of bed elevation of 30-45º, oral care, administration of medication (antibiotics/prophylaxis), and implementation of IPC measures were important nursing interventions in the prevention of VAP (17,18,19). However, contrary to our ndings, studies from the USA, and Australia showed additional strategies such as avoiding intubation, preventing re-intubation, use of sedation protocols, early initiation of enteral feeding, oral care with toothbrush and chlorhexidine, non-invasive positive pressure ventilation prone position, and changing ventilator circuits when soiled were the common strategies used to prevent VAP (8, 20).…”
Section: Strategies Used For Preventing Vap Among Critically Ill Pati...supporting
confidence: 54%
“…A prospective observational study, involving patients from 27 ICUs in nine European countries, reported that VAP resulted in 6% higher mortality, longer ICU length-of-stay (10 and 12 days), and increased duration of mechanical ventilation ( 35 ). Furthermore, systematic reviews with meta-analysis of randomized controlled trials revealed that VAP occurrence increased the ICU length-of-stay and duration of mechanical ventilation ( 36 , 37 ). This might explain the reason why most of our study population with a confirmed VAP had an ICU length-of-stay of more than 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results from a study conducted in India revealed that assessment of redness to extubate, trial extubation, maintenance of ETT cuff pressure, and suctioning were the roles in preventing VAP. (19) Furthermore, the study has revealed early weaning, head of bed elevation of 30-45º, oral care, administration of medication (antibiotics/prophylaxis), and implementation of IPC measures as the common nursing interventions for VAP prevention. This shows that nurses were implementing the VAP bundle components in their setting, In support of the Original article PAJEC above findings, previous work from India, USA, and Spain revealed that early weaning, head of bed elevation of 30-45º, oral care, administration of medication (antibiotics/prophylaxis), and implementation of IPC measures were important nursing interventions in the prevention of VAP.…”
Section: Strategies Used For Preventing Vap Among Critically Ill Pati...mentioning
confidence: 99%